2022
DOI: 10.52547/johe.11.2.114
|View full text |Cite
|
Sign up to set email alerts
|

The Moderating Role of Existential Thinking in the Association between Health Anxiety and Nurse Empathy with Covid-19 Patients

Abstract: Background: Nurses' direct exposure to COVID-19 patients and resulting health anxiety can threaten their performance of human and moral duties. Materials and Methods: This work was a descriptive correlational study. The statistical population was all nurses working in the intensive care unit of COVID-19 patients in Ardabil hospitals in the 2021 year, from which 150 people were selected by convenient sampling. Data were collected using the Health Anxiety Inventory, Scale for Existential Thinking, and the Jeffer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“… 4 After the announcement of the COVID‐19 pandemic, the virus control approach in all countries was seriously included in the agenda of governments and international health officials. 5 , 6 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“… 4 After the announcement of the COVID‐19 pandemic, the virus control approach in all countries was seriously included in the agenda of governments and international health officials. 5 , 6 …”
Section: Introductionmentioning
confidence: 99%
“…In January 2020, the World Health Organization (WHO) issued a statement declaring the novel coronavirus to be the sixth leading cause of public health emergency worldwide 4 . After the announcement of the COVID‐19 pandemic, the virus control approach in all countries was seriously included in the agenda of governments and international health officials 5,6 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study is in accordance with previous research that examines the direct and indirect impacts of existential thinking on the severity of mourning experienced by families of those who have passed away from Covid-19. Studies (Brassai et al, 13 Dargahi et al, 14 and Mason et al) 15 have demonstrated that an existential mindset can promote beneficial behaviors, such as improving distress…”
Section: According Tomentioning
confidence: 99%
“…12 Furthermore, the existential attitude can stimulate healthy behaviors by encouraging individuals to search for the meaning of life and suffering. 13 Studies have also demonstrated that existential thinking plays a mediating role in the relationship between death anxiety and empathy with COVID-19 patients 14 and can enhance the quality of working life for those involved in caring for dying patients. 15 The lifestyle changes and intense grieving experienced by individuals who have lost loved ones due to COVID-19 have led to an increase in mental health-related problems among the family members of the deceased, which is a cause for concern.…”
Section: Introductionmentioning
confidence: 99%